Cultural values in commercials: Reaching and representing the multicultural market? - Koeman, Joyce (comm, 2007)
Abstract Advertisers in the Netherlands and Flanders are discovering marketing opportunities to market to specific target groups such as children and adolescents, and their growing numbers in the ethnic minority population. There have been relatively few empirical studies on the portrayal of these audience segments. In light of the first steps in ethnic marketing theory and practice in the Netherlands and Flanders, this study questions how advertising campaigns actually deal with ethnicity and the multicultural market. This issue is tackled by means of a quantitative and comparative content analysis of Dutch, Flemish, American, Turkish, and Chinese television commercials. The first section of this article sketches a theoretical framework for the measurement of cultural values and the representation of ethnic minorities in commercials. On the one hand it draws on previous cross-cultural research examining the individualism/collectivism dimension of culture (cf. Hofstede, 1991; Schwartz, 1992; Gudykunst, 1998) and on the other hand on advertising research concerned with both content-related, and style characteristics of commercials (e. g., De Pelsmacker and Geuens, 1997). In the second section, the methodology is discussed through an examination of the sample and coding instrument. The results section reveals both similarities and differences in the use of values and communication styles in commercials from individualistic as well as collectivistic cultures. Finally, the conclusions of this study are discussed and recommendations for further research are presented.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTUxNS9jb21tdW4uMjAwNy4wMTM